Analysis of Electrical Characteristics of Pd/n-Nanocarbon/p-Si Heterojunction Diodes: By C-V-f and G/w-V-f. (17th July 2020) - Zkria, Abdelrahman; Abubakr, Eslam; Sittimart, Phongsaphak; Yoshitake, Tsuyoshi
Abstract : Diamond films are candidate for a wide range of applications, due to their wide band gap, high thermal conductivity, and chemical stability. In this report, diamond-based heterojunction diodes (HJDs) were fabricated by growing n -type nanocarbon composite in the form of nitrogen-doped ultrananocrystalline diamond/amorphous carbon (UNCD/a-C:H:N) films onto p -type Si substrates. X-ray photoemission and the Fourier transform infrared spectroscopies were employed to examine the contribution of nitrogen atoms from the gas phase into the deposited films. The results indicate the incorporation of nitrogen atoms into the grain boundaries of UNCD/a-C:H film by replacing hydrogen atoms. The capacitance- ( C - V - f ), conductance- ( G / ω - V - f ), and series resistance-voltage characteristics of the fabricated Pd/ n -(UNCD/a-C:H:N)/ p -Si HJDs were studied in the frequency range of 40 kHz-2 MHz. The existence of interface states (N ss ) and series resistance (R s ) were attributed to the interruption of the periodic lattice structure at the surface of the fabricated junction as well as the defects on the (UNCD/a-C:H:N)/Si interface. By increasing the frequency (≥500 kHz), the N ss reveals an almost frequency-independent behavior, which indicates that the charges at the interface states cannot follow ac signal at higher frequency. The obtained results demonstrated that the UNCD/a-C:H:N is a promising n -type semiconductor for diamond-based heterostructure diodes.